Educación del ecoturismo en las áreas protegidas: una meta urgente hacia la conservación del patrimonio natural - Rojas-González, Carmen Ma. (2012)
Costa Rica is home to 169 protected areas which represent 26.3% of the land surface. In 2008, approximately 60% of total tourism in Costa Rica was for recreational purposes (ICT, 2009), and one of the main attractions for this tourism was the natural beauty, diversity, and heritage of these protected areas. On the other hand, there is increasing rate of biodiversity loss (such as threatened species including felids, manatees, tapirs, spider monkeys, sea turtles, and green macaws). With the large number of tourists both domestic and international that visit protected areas within Costa Rica, there is a real opportunity for education about the natural resources and natural heritage; yet, there are minimal education activities in protected areas. This article is a call to action to develop traditional and creative educational activities to develop awareness of conservation issues that threaten the natural heritage of Costa Rica.